IMPLEMENTASI PENDIDIKAN KARAKTER INTEGRITAS DI MADRASAH IBTIDIAYAH AL-FATTAH KOTA MALANG - Anifatul Izzah; Anwar Sa'dullah; Zuhkhriyan Zakaria (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Character education is a basic guideline for someone to behave in everyday life. Along with the development of the era of character education into the spotlight, due to the emergence of problems relating to character education. These problems encourage the existence of the PPK Movement with the aim of strengthening the character of students in schools. This journal describes the implementation of integrity character education, in accordance with the existing problems in the field, namely about the integrity character of students of Madrasah Ibtidaiyah Al-Fattah, Malang City. Integrity is one of the five core values of PPK. This study uses a qualitative approach to the type of case study research. Stages of data collection techniques using observation, interviews and documentation. The results of the first study showed the attitude of students' integrity character found good characters and negative characters, the second is implementation, containing goals and objectives, forms of implementation, evaluation methods and systems. Supporting and inhibiting factors are influenced internally and externally.